Knowledge, Perceptions, and Attitudes Towards Dementia Among Medical Students in Pakistan - Muhammad Ahsan; Kainat Anwer; Hassan Raza; Saba Ali; Muazzam Ali; Parveen Akhter (Indonesian Journal of Community and Special Needs Education, 2022)
The objective of this research was to assess the participants' knowledge and attitudes towards dementia and older people in a broader manner. A Dementia education workshop for undergraduate students was held. Students fill out a questionnaire before and after the workshop.  The Questionnaire was prepared by deep insights into previous literature to determine the knowledge and attitudes of 221 participants towards dementia. Attitudes towards individuals with dementia have shown substantial positive improvements before and after the workshop, while attitudes towards older people have not been affected. Respondents were reasonably well-known general dementia but had little awareness of particular risk factors.  A significant percentage of participants thought dementia symptoms could ameliorate even at an early stage of the illness for individuals who were diagnosed with dementia. Medical and nursing students require more professional, practical, and theoretical skills and learning in their studies. It is equally essential for students, via workshops such as this one, that they get to know the humanistic aspects of illnesses and situations. Fresh thinking and additional resources may be required to combat continued widespread misunderstandings and stigma development towards dementia.